1987
DOI: 10.1021/bi00381a024
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of the octameric bifunctional enzyme formiminotransferase-cyclodeaminase in urea. Isolation of two monofunctional dimers

Abstract: Partial denaturation of the circular octameric bifunctional enzyme formiminotransferase-cyclodeaminase in increasing urea concentrations leads to sequential dissociation via dimers to inactive monomers. In potassium phosphate buffer, dissociation to dimers in 3 M urea coincides with loss of both activities and a major decrease in intensity of intrinsic tryptophan fluorescence. In the presence of folic acid, these dimers retain the deaminase activity, but with folylpolyglutamates, both activities are protected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…It has been shown that each subunit of the octameric FTCD consists of an N-terminal transferase and a C-terminal deaminase active site, separated by a short linker sequence (51). Both domains self-dimerize, confirming that FTCD octamers include two different types of subunit interfaces which are most likely maintained for expression of both activities (52,53). It has been suggested that the polyglutamate-binding site resides at the subunit interface formed between the deaminase domains (51).…”
Section: Discussionmentioning
confidence: 79%
“…It has been shown that each subunit of the octameric FTCD consists of an N-terminal transferase and a C-terminal deaminase active site, separated by a short linker sequence (51). Both domains self-dimerize, confirming that FTCD octamers include two different types of subunit interfaces which are most likely maintained for expression of both activities (52,53). It has been suggested that the polyglutamate-binding site resides at the subunit interface formed between the deaminase domains (51).…”
Section: Discussionmentioning
confidence: 79%
“…Biochemical properties of porcine FTCD have been extensively studied, and the enzyme exists as a planar ring (ϳ12 nm in diameter) of eight identical subunits (23), relatively resistant to chymotryptic digestion (37). To examine the proteolytic behavior of rat FTCD, the SG fraction was subjected to proteinase K treatments in the absence or presence of 6.5 M urea as a denaturing reagent.…”
Section: K Is Tightly Associated With Golgi Membranes-previousmentioning
confidence: 99%
“…Previous analysis has indicated that porcine FTCD exists as a dimer organized into higher order structures, tetramers and octamers (37). To determine whether rat FTCD shows similar structural characteristics, rat liver cytosolic fraction was either untreated or subjected to cross-linking, analyzed by SDS-PAGE in the presence or absence of reducing agent, and, after transfer to nitrocellulose filters, immunoblotted with mAb 58K-9.…”
Section: K Is Tightly Associated With Golgi Membranes-previousmentioning
confidence: 99%
“…Given that moonlighting functions can depend on differences in protein-protein interactions (48), it seems possible that running these opposing reactions concurrently is facilitated by FT joining/not joining a protein complex related to histidine degradation. In this connection, it is relevant that mammalian FT-CD is an octamer that can dissociate into two types of monofunctional dimers, and that while the FT and CD activities of the octamer function separately with monoglutamylated folates, polyglutamates are channeled from the FT to the CD active site (34,53). Analogous behavior of prokaryote FT oligomers, or perhaps FT-CD complexes, together with polyglutamate-mediated channeling between FT and CD reactions, could result in the functional partitioning, i.e.…”
Section: Discussionmentioning
confidence: 99%